Changes in streamflow regimes and their responses to different soil and water conservation measures in the Loess Plateau watersheds, China. Issue 10 (19th October 2021) - Zhang, Shuyu; Zhao, Guangju; Mu, Xingmin; Tian, Peng; Gao, Peng; Sun, Wenyi
Abstract: Investigating the changes in streamflow regimes in response to various influencing factors contributes to our understanding of the mechanisms of hydrological processes in different watersheds and to water resource management strategies. This study examined streamflow regime changes by applying the indicators of hydrologic alteration method and eco‐flow metrics to daily runoff data (1965–2016) from the Sandu, Hulu and Dali Rivers on the Chinese Loess Plateau, and then determined their responses to terracing, afforestation and damming. The Budyko water balance equation and the double mass curve method were used to separate the impacts of climate change and human activities on the mean discharge changes. The results showed that the terraced and dammed watersheds exhibited significant decreases in annual runoff. All hydrologic metrics indicated that the highest degree of hydrologic alteration was in the Sandu River watershed (terraced), where the monthly and extreme flows reduced significantly. In contrast, the annual eco‐deficit increased significantly, indicating the highest reduction in streamflow among the three watersheds. The regulation of dams and reservoirs in the Dali River watershed has altered the flow regime, and obvious decreases in the maximum flow and slight increases in the minimum flow and baseflow indices were observed. In the Hulu River watershed (afforested), the monthly flow and extreme flows decreased slightly and were categorized as low‐degree alteration, indicating that the long‐term delayed effects of afforestation on hydrological processes. The magnitude of the eco‐flow metrics varied with the alteration of annual precipitation. Climate change contributed 67.47% to the runoff reduction in the Hulu River watershed, while human activities played predominant roles in reducing runoff in the Sandu and Dali River watersheds. The findings revealed distinct patterns and causes of streamflow regime alteration due to different conservation measures, emphasizing the need to optimize the spatial allocation of measures to control soil erosion and utilize water resources on the Loess Plateau. Abstract : Streamflow regimes changed greatly due to various soil conservation measures in three watersheds. Human activities played a predominant role in the significant reduction in runoff in the terraced and dammed watersheds. Streamflow remained relatively stable and was sensitive to climate change in the afforested watershed.